Effect of unusually elevated SO2 atmospheric content on the corrosion of high power electrical conductors - Part 3. Pure copper - Vera, Rosa (2008)
This research work belongs to a series of studies simultaneously performed with two previous publications in this journal as Part I. Al and 6201 Al alloy and Part 2. Pure copper. The aim of the project was to have a comparative picture of the joint effect of marine and industrial atmospheric pollutants on the corrosion resistance of wire metals employed for high power electric transmission. This one is also based on the pure Cu behaviour, but limited to six marine-industrial atmospheres with extremely high SO2 contents. The interest in this study was triggered by unusual results considered appropriate to investigate. Weight loss after 4 and 11 months exposure was determined and morphology of the attack was analysed through SEM-ESEM-EDX. Polarisation of samples after exposure to all the test sites as compared to bare Cu clarified the effect of unusually high SO2 pollutant contents in these atmospheres on the high protectiveness of the corrosion products formed.